Kajian Karakteristik Finansial Pkl Malioboro Dengan Analisis Cluster - Damayanti, Dila; Asteria, Beta (JURNAL RISET MANAJEMEN SEKOLAH TINGGI ILMU EKONOMI WIDYA WIWAHA PROGRAM MAGISTER MANAJEMEN, 2015)
This study uses primary data which includes the identity of the industry, capital aspects, liquidity aspects, leverage aspect, profitability aspect, and other supporting aspects. The primary data is obtained through filling the questionnaire by respondents with the population of the entire population of Malioboro street vendors or census sampling with consideration that Malioboro street vendors are not so many (limited). Financial condition can be seen from various aspect, including liquidity aspect, leverage aspect and profitability aspect. As for knowing the financial characteristics possessed by each Malioboro street vendors,it is necessary to classify Malioboro street vendors based on financial characteristics that can be done by using a clustering method. In the clustering stage, groups each of which member has similar or identical financial characteristics will be obtained. These characteristics are utilized as the basis for determining financial strategies by using SWOT analysis which can be developed for each cluster of Malioboro street vendors. Based on the clustering, two categories of cluster Malioboro street vendors are obtained, namely Weak Financial Cluster and Strong Financial Cluster. Based on the financial characteristics of each cluster, several strategies related to financial strengthening Malioboro street vendors can be recommended. Strategies that can be developed for Strong Financial Cluster is optimal cash strategy and capital formation strategy.Key words: Street vendors, financial characteristics, cluster, SWOT